EUROPEAN ADMINISTRATIVE STANDARDS AND PUBLIC ADMINISTRATION IN THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2018)
After the introductory remarks which, among others, stipulate that the reform and modernization of public administration come from the state autonomy of the Republic of Croatia in the 90s of the previous century and the efforts to go in the path of the western democracies, the author exposes on public administration, local and regional self-government and legal entities with public authorities. Moreover, each of the stipulated segments of public administration is further analysed on the basis of legal structure, current situation and goals and measures for improvement planned by the strategic document of development of Croatian public administration between 2015 and 2020. The author considers new legal regulations on general administrative proceeding and administrative judiciary and subsequently explores the administrative standards of the European Union with key standard being the administrative cooperation among the member states. Croatia has to strengthen the administrative capabilities and develop the standards of European good administrative practice and thus accomplish the necessary Europeanisation of public administration.